Knowledge About Chronic Kidney Disease In Hemodialysis Patients - Heringer, Tiago Antonio (2021)
Objective: To verify the degree of knowledge and the source of information about kidney disease in patients with Chronic Kidney Failure undergoing treatment at a hemodialysis clinic.Materials and Methods: The knowledge of these patients was assessed in an exploratory and descriptive study carried out through a questionnaire applied to 58 patients, of both sexes, in a renal clinic in the Northwest of Rio Grande do Sul.Results: We demonstrated that the majority of patients search for information about Chronic Kidney Failure on the internet and that less than half seek this information from health professionals. When the search is carried out with health professionals, the nurse predominates. Patients demonstrated little knowledge regarding the medications they use, but most were able to report the foods they should avoid and the amount of water they can drink.Conclusion: We show that most patientsÂ are aware of their condition and treatment, but even so, some still disobey the dietary rules. Health professionals are not the main patient of information for patients, showing weaknesses in the professional-patient relationship.